2018
DOI: 10.1186/s13063-018-2644-1
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for abdominal pain relief in patients with acute pancreatitis: study protocol for a randomized controlled trial

Abstract: BackgroundPrevious studies have shown that electroacupuncture (EA) reduces the severity of acute pancreatitis. However, the effect of EA for pain relief in patients with acute pancreatitis has not been evaluated yet. The purpose of this study was to prove the efficacy of EA for pain relief in patients with acute pancreatitis compared with conventional treatment.MethodsThis study is a randomized, controlled, three-arm, parallel-group, multi-center trial. Patients diagnosed with acute pancreatitis are enrolled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Wang et al 14 found that mirabilite promoted the recovery of intestinal mucosal permeability and prevented of sepsis acute gastrointestinal injury in patients with severe sepsis. Animal experiments have shown that Dachengqi decoction, famous formulas in China which comprises mirabilite serving as the principal component increases cell viability, induces pancreatic acinar cell apoptosis, reduces acinar necrosis and protects from injuries to the pancreas in vivo and in vitro 15,16 . The likely mechanisms may operate through reducing ROS generation and regulating the nitric oxide pathway in rat with acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 14 found that mirabilite promoted the recovery of intestinal mucosal permeability and prevented of sepsis acute gastrointestinal injury in patients with severe sepsis. Animal experiments have shown that Dachengqi decoction, famous formulas in China which comprises mirabilite serving as the principal component increases cell viability, induces pancreatic acinar cell apoptosis, reduces acinar necrosis and protects from injuries to the pancreas in vivo and in vitro 15,16 . The likely mechanisms may operate through reducing ROS generation and regulating the nitric oxide pathway in rat with acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%